2020
DOI: 10.3390/medicina56100519
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor as an Alternative Antiplatelet Therapy in Cardiac Patients Non-Sensitive to Aspirin

Abstract: Background and Objectives: Aspirin (acetylsalicylic acid—ASA) is a first-line antiplatelet therapy provided to patients with coronary artery disease (CAD). However, it has been demonstrated that 20–30% of these patients are non-sensitive to their ASA therapy. ASA non-sensitivity is a phenomenon where low-dose ASA (81–325 mg) does not completely inhibit arachidonic-acid-induced platelet aggregation, putting patients at risk of adverse cardio-thrombotic events. Ticagrelor is a P2Y12 receptor inhibitor and altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…ASA non-sensitivity has become a well-known and prevalent issue, with anywhere between 20 and 30% of patients at risk of further adverse cardiovascular events due to the failure of ASA to completely inhibit platelet aggregation. Previous studies have reported that 15% of patients with atherosclerotic vascular disease were non-sensitive to their prescribed 81 mg ASA therapy, and a further 32% of patients with cardiovascular risk factors were also non-sensitive to ASA [ 11 , 12 ]. There are two main mechanisms of ASA non-sensitivity: (1) pharmacokinetic variability in patients’ response to ASA—for example reduced absorption within the gastrointestinal tract, higher ASA metabolism, or increased platelet turnover; (2) pharmacodynamic differences such as genetic polymorphisms leading to structural changes in the COX enzyme [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASA non-sensitivity has become a well-known and prevalent issue, with anywhere between 20 and 30% of patients at risk of further adverse cardiovascular events due to the failure of ASA to completely inhibit platelet aggregation. Previous studies have reported that 15% of patients with atherosclerotic vascular disease were non-sensitive to their prescribed 81 mg ASA therapy, and a further 32% of patients with cardiovascular risk factors were also non-sensitive to ASA [ 11 , 12 ]. There are two main mechanisms of ASA non-sensitivity: (1) pharmacokinetic variability in patients’ response to ASA—for example reduced absorption within the gastrointestinal tract, higher ASA metabolism, or increased platelet turnover; (2) pharmacodynamic differences such as genetic polymorphisms leading to structural changes in the COX enzyme [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Antithrombotic Trialists Collaboration demonstrated that ASA is effective in reducing adverse cardiovascular events by approximately 20% [ 6 ]. However, an alarming 20–30% of patients with atherosclerotic disease suffer from ASA non-sensitivity, where ASA fails to prevent adverse cardiovascular events [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…LTA was conducted as described above. Patients were considered aspirin non-sensitive if they had a maximal platelet aggregation of ≥20% when activated with arachidonic acid, as per previous studies ( 8 , 13 17 , 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been documented that ~20–30% of patients are resistant to their aspirin therapy, with some studies determining resistance to be as high as 60% in their respective patient population [ 36 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Recent studies suggest that aspirin resistance increases the risk of adverse cardiovascular events by almost three-fold in various patient populations [ 38 , 46 , 52 ].…”
Section: Aspirin Resistancementioning
confidence: 99%
“…In LTA analysis, light transmission is proportional to platelet aggregation and hence can provide the total percentage of platelets aggregated in response to the platelet agonist of interest. LTA can be a useful method for invitro platelet testing, as a wide range of platelet activation pathways can be investigated using different agonists such as arachidonic acid, ADP, and thrombin, and plasma samples can be incubated with drugs of interest before testing in order to study the effects of these drugs on platelet aggregation [ 51 , 58 ]. Therefore, in patients taking antiplatelets, aggregation is expected to remain around 0%, and those who are not taking any antiplatelet therapy, the light transmission is expected to increase to approximately 100% [ 59 , 60 ]…”
Section: Antiplatelet Resistance Function Testsmentioning
confidence: 99%